Nurse-led visionary leadership in healthcare : excellence in practice, policy, and ethics - Wei, Holly, 1966-; Horton-Deutsch, Sara; Sigma Theta Tau International (Indianapolis, IN : Sigma Theta Tau International, 2022)
'The world is constantly changing, and during a time of great challenges, our healthcare systems must evolve-moving beyond an illness narrative and toward one that focuses on health and healing. In doing so, our leadership styles must evolve as well. Nurse-Led Visionary Leadership in Healthcare informs, expands, and empowers nurse leaders to envision and transform the current healthcare system using an evolved worldview to achieve a global, life-sustaining perspective. Lead authors and editors, Holly Wei and Sara Horton-Deutsch model their call to move away from hierarchical leadership to more engaged, open, equitable, inclusive, authentic, and caring leadership styles'--
THE EVOLUTION OF LEADERSHIP THEORIES -- GLOBAL PERSPECTIVES ON THE EVOLUTION OF NURSING LEADERSHIP -- TRANSCENDING LEADERSHIP AND REDEFINING SUCCESS -- DEVELOPING EFFECTIVE NURSING LEADERSHIP SKILLS AND CAPACITY -- NURTURING HEALTHY AND HEALING WORK ENVIRONMENTS -- LEADERSHIP ROLES IN PROMOTING A RESILIENT WORKFORCE -- LEADERSHIP ROLES IN MITIGATING ORGANIZATIONAL TRAUMA -- NURSING LEADERSHIP IN PLANETARY AND ENVIRONMENTAL HEALTH -- QUANTUM CARING LEADERSHIP : A NEW ONTOLOGY INTO PRACTICE -- CARING SCIENCE INFORMED LEADERSHIP -- PROMOTING EXCEPTIONAL PATIENT EXPERIENCE THROUGH COMPASSIONATE CONNECTED CARE -- APPLYING COMPLEXITY SCIENCE IN PROMOTING COMMUNITY AND POPULATION HEALTH -- ASSEMBLING A UNIFYING FORCE : INTERPROFESSIONAL COLLABORATION TO IMPROVE HEALTHCARE -- LEADERSHIP IN DISASTER PREPAREDNESS AND RESPONSE -- NURSING LEADERSHIP IN THE GLOBAL HEALTH CONTEXT -- NURSING LEADERSHIP IN PROMOTING THE USE OF EVIDENCE -- WISDOM LEADERSHIP : A DEVELOPMENTAL JOURNEY -- DIVERSITY, EQUITY, AND INCLUSION IN NURSING EDUCATION AND HEALTH SYSTEMS -- TRANSFORMING HEALTH POLICY -- NURSING LEADERSHIP IN SOCIAL AND POLITICAL DETERMINANTS OF HEALTH -- CREATING A CONNECTED WORLD : A CALL TO ETHICS OF FACE AND BELONGING.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Added to collection customer.56279.3
Keywords: Leadership; Nurse administrators; Leadership; Nurse's Role; Nursing, Supervisory; Nurse Administrators; Nursing -- organization & administration; Leadership; Infirmières en chef; Leadership; Nurse administrators; Electronic books